Analysis Of The JIS Development Conflict: Eviction Of Bayam Village Residents And The Disregard Of 'Right To Have Rights' - Shakira, Bella Ola; Zahra Hanifah Salma; Revalyza Misbah; Aniqotul Ummah (PT ARRUS Intelektual Indonesia, 2024)
Jakarta International Stadium (JIS) is a large-scale infrastructure project designed to be one of the largest and most modern stadiums in Indonesia, with a capacity of up to 82,000 spectators. This research analyzes the social conflict caused by the eviction of Kampung Bayam residents for the construction of the Jakarta International Stadium (JIS) from the perspective of social justice and human rights. This study aims to explore how the eviction not only reflects a violation of the right to housing, but also a denial of the collective rights of the community, including the right to development that affects their lives. This study uses a qualitative-descriptive approach with secondary data from official documents, previous research, and mass media. The results show that the evictions not only resulted in the loss of people's homes and livelihoods, but also violated basic principles of social justice, such as the right to housing and participation in development. This denial of basic rights creates significant socio-economic impacts, including psychological trauma, difficulty accessing public services, and loss of economic stability. This research recommends inclusive and socially just development policies to ensure no group of people is marginalized.